2010
DOI: 10.1122/1.3302451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inkjet fluid’s performance using the “Cambridge Trimaster” filament stretch and break-up device

Abstract: This paper describes the design and initial results from the "Cambridge Trimaster," a recently developed high speed filament stretch and break-up device that can be used for viscoelastic fluids with shear viscosities as low as 10 mPa s. Extensional viscosity and filament break-up behavior were studied optically using a high speed camera and extensional viscosity values determined for a series of mono-disperse polystyrene solutions up to a weight concentration of 5 wt % were measured as a function of the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 35 publications
7
108
1
Order By: Relevance
“…Although the breakup of the plasma filament looks similar to that of a Newtonian fluid, the thin tails close to the top and bottom plates, indicated by the arrow in Figure 4b1 and 4b2, suggest a slight viscoelastic behavior of human plasma. A similar filament shape was observed in the filament thinning and breakup of weakly elastic fluids, in which the formation of a tail indicates that viscoelasticity acts against the breakup by increasing the breakup time [36,37]. Nevertheless, the very weak viscoelastic character of human plasma seen here contrasts with previous observations of Brust et al [19].…”
Section: Figcontrasting
confidence: 57%
“…Although the breakup of the plasma filament looks similar to that of a Newtonian fluid, the thin tails close to the top and bottom plates, indicated by the arrow in Figure 4b1 and 4b2, suggest a slight viscoelastic behavior of human plasma. A similar filament shape was observed in the filament thinning and breakup of weakly elastic fluids, in which the formation of a tail indicates that viscoelasticity acts against the breakup by increasing the breakup time [36,37]. Nevertheless, the very weak viscoelastic character of human plasma seen here contrasts with previous observations of Brust et al [19].…”
Section: Figcontrasting
confidence: 57%
“…Therefore, the initial experimental filament stretch strain rate was calculated to be 76 s -1 for the experiments in this chapter. Vadillo et al (2010) reported that measurement of extensional viscosity was independent of the initial filament stretch strain rate of the experiment.…”
Section: Background To Extensional Deformation Calculationsmentioning
confidence: 99%
“…ROJER or other related capillary-thinning methods for extensional rheometry (such as CaBER or modified versions of CaBER [38][39][40], exploit the dynamics of the Rayleigh-Plateau instability and often rely on optical devices such as high-speed/strobe cameras, lenses and bright field illumination strategies to record the evolution in the filament diameter with time. A liquid thread with a known initial radius R that is connected at both ends to hemispherical liquid reservoirs (as in either of the ROJER/CaBER configurations) experiences higher capillary pressures inside the filament neck compared to the pressure in the hemispherical reservoirs.…”
Section: B Limits Of Rojermentioning
confidence: 99%
“…Knowing the limits of the commercial CaBER instrument when measuring the extensional rheology of dilute solutions, several extensions and alternate protocols have been introduced in the literature. The Slow Retraction Method (SRM) 38 and Cambridge Trimaster 39,40 are devices similar to CaBER that also utilize capillary thinning but show a substantial improvement in the range of measured elongational relaxation times (down to s E ' 80 ls). A more recent approach 7 has reintroduced an old concept based on studying the capillary breakup of a thin viscoelastic liquid jet.…”
Section: Introductionmentioning
confidence: 99%